American policy in the Far East, 1931-1940 - Bisson, T. A. (International secretariat, Institute of Pacific relations, 1939)
This book introduce the manchurian crisis 1931 - 1933. Japanese pressure on resurgent China 1933 - 1937. Collapse of naval limitation. Japanese - American trade friction 1933 - 1936...